The design and development of semi-automated paste filling machine for spicy shrimp paste - Sharif Z.M.; Rahim M.Z.; Ibrahim M.R.; Othman M.S. (Science and Engineering Research Support Society, 2023)
The main objective of the development of semi-automated paste filling machine was to provide the simple filling mechanism into pouch pack for spicy shrimp paste (sambal belacan). The spicy shrimp paste contains chilly seed and flakes often stuck during filling process whilst using the current and normal filling machine. Hence, semi-automated paste filling machine for spicy shrimp paste was developed and customized for Dapur Ibu Food Industry. The machine is 70cm height X 35cm width X 83cm length. The development of this machine attached with volume sensor, speed sensor and extruder (co-injection) to push the spicy shrimp paste through the special fabricated nozzle and avoid clotting during the process of filling into the pouch pack. The co-extrusion could create the outer envelope and an auxiliary system for injection a filling. The machine also has sensor for speed depends on the speed of the operator holding the pouch pack. Quality control for food hygienic whilst the operation is ongoing is being controlled and monitored. 2019 SERSC.